Multi-target action of Garcinia livingstonei extract and secondary metabolites against fatty acid synthase, α-glucosidase, and xanthine oxidase - Azza M. Abdul-Rahman; Ahlam Elwekeel; Reem S. Alruhaimi; Emadeldin M. Kamel; Albandari Bin-Ammar; Ayman M. Mahmoud; Abeer S. Moawad; Mohamed A. Zaki (Saudi Pharmaceutical Journal, 2023)
Garcinia livingstonei is a traditional herbal medicine that showed beneficial health effects and bioactivities. Four compounds have been isolated from the plant leaves and were elucidated as lupeol, betulin, podocarpusflavone A, and amentoflavone. The inhibitory activities of G. livingstonei extract and isolated metabolites against fatty acid synthase (FAS), α-glucosidase, and xanthine oxidase (XO) were investigated in vitro. The affinity of the compounds toward the studied enzymes was investigated in silico. The plant extract inhibited FAS, α-glucosidase, and XO with IC50 values of 26.34, 67.88, and 33.05 µg/mL, respectively. Among the isolated metabolites, betulin exhibited the most inhibitory activity against α-glucosidase and XO with IC50 values of 38.96 and 30.94 µg/mL, respectively. Podocarpusflavone A and betulin were the most potent inhibitors of FAS with IC50 values of 24.08 and 27.96 µg/mL, respectively. Computational studies corroborated these results highlighting the interactions between metabolites and the enzymes. In conclusion, G. livingstonei and its constituents possess the potential to modulate enzymes involved in metabolism and oxidative stress.